KINERJA MODEL PERKERASAN JALAN DENGAN BLOK PENGAKU - Marjono , (Prokons: Jurnal Teknik Sipil, 2019)
One of the factors causing the cracking of rigid pavement surfaces for roadways is the occurrence of tensile stresses due to vehicle wheel loads that exceed the tensile stresses of the concrete, if not handled immediately will affect the service life of pavement construction.This research is conducted to get alternative solution from pavement construction problem, that is damage before end of service period. One of the efforts that can be done is to make a model of pavement construction that can reduce the tensile stress on the underside of the concrete plate by adding a stiffening block on the underside of the concrete plate for road pavement. The results of this study are expected to be one form of innovation from rigid pavement construction that can be applied in Indonesia.  On the basis of this then the researchers took the title "Performance Pavement Pavement Construction Model with the Confession Block".The purpose of this research is to know the effect of the addition of the stiffening block on the pavement construction model with the stiffening block, compared to the pavement model without the stiffening block, in terms of the number of load repetitions and the cracking patterns occurring on the surface of the concrete plate.Pursuant to result of research with experimental method on pavement model with size of width 50 cm, length 50 cm and thickness 3 cm. Data obtained that the performance of pavement model with the stiffening block, able to reduce crack width by 41.82%. Maximum load repetition on pavement model with Type I block 31.33% higher than the maximum load repetition on pavement model without stiff block (Type II). The damage patterns that occur in Type I pavement models, beginning with cracks in the corners, followed by cracking in the middle until the plate is split. For the Type II pavement model, the crack occurs at an angle, and immediately splits.Keywords: rigid pavement, loop load, surface crack, compressive strength